Implementação do júri no Brasil: debates legislativos e estudo de caso (1823-1841) - Viviane Penha Carvalho Silva (2011)
This research discusses the implementation of the jury system in Brazil occurred in the first decades of the nineteenth century. The reported time (1823-1841) stands at a transitional moment, and therefore to experiment with new organizational forms, when fledgling institutions seeking to consolidate. Among this transition, the focus of this work: the novelty of peer review that although originate with limited powers, has been guaranteed as a constitutional right (1824) and regulated by the expanding jurisdiction with the first Brazilian Code of Procedures (1832). The topic was approached from two strands that are complementary: the first focuses on the political process of expanding the legal powers of the jury trial of all crimes, and second, how the jury constituted a socioeconomically and served community particular, the so-called Term of the town São José del-Rei.